Understanding the long-term impact of prescribed burning in mediterranean-climate biodiversity hotspots, with a focus on south-Western Australia - Bradshaw, S.; Dixon, Kingsley; Lambers, H.; Cross, Adam; Bailey, J.; Hopper, S. (CSIRO PUBLISHING, 2018)
© IAWF. Wildfires are expected to increase worldwide both in frequency and intensity owing to global warming, but are likely to vary geographically. This is of particular concern in the five mediterranean regions of the world that are all biodiversity hotspots with extraordinary plant and animal diversity that may be impacted by deliberately imposed fire. Wildland managers attempt to reduce the impact and mitigate the outcomes of wildfires on human assets and biodiversity by the use of prescribed burning. The response that we must 'fight fire with fire' is understandable, perceived as reducing the flammability of wildlands in fire-prone regions and lessening the impact of wildfires. The long-term impact on biodiversity is, however, less clear. The practice of prescribed burning has been in place and monitored in south-Western Australia for 50 years, longer and more intensively than in most other mediterranean ecosystems. The present target is for 200 000 ha burned each year in this biodiversity hotspot. Published studies on the impact of this burning on infrastructure protection and on biodiversity are here used to understand the protective capacity of the practice and to foreshadow its possible long-term ecological impact across all mediterranean ecosystems.